Mid-term Outcomes of the Subchondroplasty Procedure for Patients with Osteoarthritis and Bone Marrow Edema. Issue 7 (21st July 2017) - Byrd, Jennifer Marie; Akhavan, Sam; Frank, Darren A.
Objectives: Bone marrow edema (BME) is a negative prognostic factor for patients with knee osteoarthritis (KOA). BME is strongly associated with pain, decreased function, structural deterioration and rapid progression to total knee arthroplasty (TKA). Subchondroplasty (SCP) (Knee Creations, Zimmer, Warsaw, IN) directly addresses BME in the setting of KOA by injecting calcium phosphate cement into the area of BME. The objective of this research was to show clinical results of the SCP procedure. Methods: A retrospective chart review with follow-up questionnaire was conducted on SCP patients in short-term and midterm (>2 years). All patients failed conservative measures and were candidates for TKA. The questionnaire addressed symptoms before and after SCP, further interventions, the perception of and willingness to undergo SCP again. Results: 133 of 143 subchondroplasty patients responded. The average patient was 57 years old (38-84 years) and 47% male. The average follow-up for short-term patients was 14.6 (4-22) months and for mid-term patients was 32.1 (24-43) months. Pain score decreased from 8.3 pre-op to 3.4 post-op in both groups. 35% in the short-term group required injections, increasing to 41% in the mid-term. The short-term group demonstrated satisfaction of 8.3 out of 10, with 82% willing to undergo SCP again and 89% recommending SCP. In the mid-term group, satisfaction increased to 8.5 with 95% willing to undergo SCP again and 96% recommending the procedure. In all, 32 patients (25%) progressed to TKA (Figure 1) at an average of 17.8 months, with 22 (69%) of these occurring before 2 years. Conclusion: SCP is an effective and well received treatment for patients with KOA and BME. In patients who failed conservative measures and were considering TKA, excellent results are seen at 2.5 years follow-up with only 25% of patients requiring TKA. Of all patients not requiring TKA, 93% would undergo SCP again and 98% would recommend it. Table l. Short and Mid-term Results of the Snhcliondroplasty Procedure Preop Short-term Mid-term All-Comers Patients 128 87 84 128 Avg, f/u 14.6 months 32.1 months 23.1 Pain Score 8.3 3.4 3.4 3.4 TKA 22 (25%) 10 (12%) 32 (25%) Avg, time to TKA 11.5 months 30.7 months 17.8 months Injections 23 (35%) 30(41%) 38 (40%) Satisfaction 8.3 8.5 8.4 Undergo Again 82% 95% 93% Recommend 89% 96% 98%